Decontamination and reuse of N95 filtering facemask respirators: a systematic review of the literature (2020)
Introduction: As has happened in other emerging respiratory pandemics, demand for N95 filtering facemask respirators (FFRs) has far exceeded their manufacturing production and availability in the context of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. One of the proposed strategies for mitigating the massive demand for N95 FFRs is their reuse after a process of decontamination that allows the inactivation of any potentially infectious material on their surfaces. This article aims to summarize all of the available evidence on the different decontamination methods that might allow disposable N95 FFRs to be reused, with emphasis on decontamination from SARS-CoV-2. Methods: We performed a systematic review of the literature in order to identify studies reporting outcomes of at least 1 decontamination method for inactivating or removing any potentially infectious material from the surface of N95 FFRs, specifically addressing issues related to reduction of the microbial threat (including SARS-CoV-2 when available), maintaining the function of N95 FFRs and a lack of residual toxicity. Results: We identified a total of 15 studies reporting on the different decontamination methods that might allow disposable N95 FFRs to be reused, including small-scale energetic methods and disinfecting solutions/spray/wipes. Among these decontamination methods, ultraviolet germicidal irradiation and vaporized hydrogen peroxide seem to be the most promising decontamination methods for N95 FFRs, based on their biocidal efficacy, filtration performance, fitting characteristics, and residual chemical toxicity, as well as other practical aspects such as the equipment required for their implementation and the maximum number of decontamination cycles. Conclusions: Although all the methods for the decontamination and reuse of N95 FFRs have advantages and disadvantages, ultraviolet germicidal irradiation and vaporized hydrogen peroxide seem to be the most promising methods.